Experimental study on the bearing property of the composite foundation with stiffened deep cement mixing pile based on the PHC pile - Feng, Tao; Huiqiang, Zhu; Fengbo, Dong; Shaoqiang, Chai; Feng, Liu; Ming, Zhang (Frontiers in Materials, 2023)
Inserting prestressed high-intensity concrete pipe pile (PHC pile) into cement-soil mixing pile can form a new composite pile, named composite foundation with stiffened deep cement mixing (SDCM) pile. The Huanghuai alluvial stratum in China is selected to carry out the in-situ test for SDCM pile, and the bearing capacity of the SDCM pile is tested by the slow-speed maintenance load method. The results show that: For the SDCM pile with the dense silt and fine sand as the bearing layer, the characteristic value of bearing capacity can reach 2300 kN. That means the SDCM pile with length of 8.0 m meets the load requirement of general high-rise building.Further analysis shows that, the SDCM pile saves more than 40% of the cost compared with the traditional CFG pile, and has better quality control advantages at the same time. This research can provide basic data and design reference for similar site foundation projects.